Optimal Hybrid Renewable Energy Integration for Reliable and Cost Efficient of Isolated System - Ardhyantoro, Novan Iman; Husnayain, Faiz (ELKHA : Jurnal Teknik Elektro, 2025)
Nusmapi Island is one of Indonesia's isolated islands that rely on Diesel Power Plant (PLTD) with a capacity of 20 kW to meet the electricity needs of its 50 customers. However, this PLTD only operates 12 hours a day due to high operational costs, reaching IDR 215,240,980/year with fuel consumption of 20,889 liters of diesel, equivalent to 17.56 tons with a COE of IDR 7,132/kWh in 2023. The reliance on diesel generators exacerbates ecological harm by releasing COâ‚‚ emissions"”a critical contradiction to Indonesia"™s nationally determined contribution (NDC) under the Paris Agreement, which mandates carbon neutrality by 2060. This research seeks to determine the most effective hybrid energy system design and configuration for Nusmapi Island, evaluating both technical feasibility and economic viability. The technical feasibility was assessed based on the unmet electric load, while the economic feasibility was evaluated using operational costs and the Cost of Energy (COE). The analysis indicates that the optimal system configuration comprises a 8,1-kW solar photovoltaic array, a 20-kW diesel generator, a 12-kW inverter, and five battery units housed within a single compartment. This configuration in real implementation will be able to produce 61,193 kWh/year, thereby increasing the power hours to 24 hours and reducing the unmet electric load to 0%. It will have a COE of IDR 3,280/kWh and will result in a fuel consumption reduction of 3,661 liters/year and operational costs of IDR 30,692,119/year. In addition, this configuration has environmental advantages with a renewable fraction reaching 18.3%